Analisis hukum Putusan Pengadilan Agama Pekanbaru yang Menghapuskan Hak Pemeliharaan Ibu Terhadap Anak Angkat Karena Kelainan Seksual - Aqilla Fadia Haya; Hazar Kusmayanti; Betty Rubiati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Divorce has an impact on children, one of the cases that shows adopted children are affected in the divorce of their adoptive parents is in the Decision of the Pekanbaru Religious Court Number 0486/Pdt.G/2018/PA.Pbr in the Decision the Petitioner requests the Court to determine child maintenance rights appoint him because the Respondent has a sexual disorder. This study aims to determine the conformity of the Panel of Judges' Decisions with related laws and regulations. Based on the results of the study, firstly that granting the right to care for adopted children who are still minors to the Petitioner is in accordance with the Marriage Law, the Child Protection Law, and the Compilation of Islamic Law, but to strengthen the considerations of the Panel of Judges, Article 45 paragraph (1) and paraghraph (2) Marriage Law, Article 13 paragraph (1) and Article 59 can be added Child Protection Act, also Article 156 letter c Compilation of Islamic Law.